Azucena - Davao, Ricky; Rivero, Dante; de Rossi, Allesandra; Mercado, Glydel; Siguion-Reyna, Carlos; Viva Films ([Manila] Viva Films, 2001)
A story about the unlikely friendship between a man who butchers dogs for a living and an adolescent dog lover.
Original music, Ryan Cayabyab ; edited by Manet Dayrit ; director of photography, Romulo Anaojo ; screenplay, Enrique Ramos ; line producer, Lino Mabalot ; produced and directed by Carlos Siguio-Reyna.
Ricky Davao, Dante Rivero, Allesandra De Rossi and Glydel Mercado.
Keywords: Feature films